Deep Back Massage dengan Lavender Oil terhadap Nyeri Persalinan di Wilayah Kerja Puskesmas Polonia - Yohana Putri Apryanti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Labor pain is a subjective experience of physical sensations associated with uterine contractions, cervical dilatation and effacement, and fetal descent during labour. One way to reduce the Maternal Mortality Rate (MMR) is through the maternal affection movement which is an aspect of the 5 common threads to help mothers feel safe and during the delivery process. Various efforts have been made to reduce pain both pharmacologically and non-pharmacologically, pharmacological methods are very important because they do not harm the mother and fetus. This study was conducted to identify the reduction of pain in first-stage labor mothers with the deep back massage method with lavender oil. This research is a quantitative study with a quasi-experimental design with a pretest-posttest design in the BPM Working Area of ​​the Polonia Health Center. The sampling technique in this study was a purposive sample with as many as 20 respondents. Pain intensity will be measured using NRS (Numeric Rating Scale). And it was found that being given a deep back massage with lavender oil had an effect on reducing labor pain and it was good to do it when the mother gave birth who had entered the active phase because it could provide physiological and psychological benefits.